"A Priest does not consider the toppling of the Shah as an option" The KGB and the revolution in Iran. Issue 4 (October 2022) - Asinovskiy, Dmitry
Abstract: This paper investigates the activities of the KGB residency in Iran during the 1978–79 revolution and early years of the Islamic Republic. While some foreign experts were quick to point to the KGB as behind the revolution, it soon became clear that Soviet leadership and intelligence were no less surprised with the events than their counterparts in the West. However, this does not mean that Moscow did not see the revolution as an opportunity. The KGB served as one of the principal tools of Soviet attempts to influence the domestic situation in Iran and, although it achieved little in pursuing its goals, KGB activities in Iran reveal the extent to which binary Cold War thinking limited Soviet leadership in dealing with the challenge of the Iranian revolution.